An Analysis of Interactional Metadiscourse in Public Speaking: A Case Study in English Speeches of the Prime Minister of Bhutan - Tashi, Tshen; Suksawas, Wannaprapha (International Journal of Engineering and Technology, 2018)
Public speaking is an act of presenting a speech to an audience with the goal of altering attitudes, actions, and sentiments, and to leave them inspired by words and impressed by meanings[1]. In general, speakers add metadiscourse markers into their speech to make it comprehensible to the audience rather than a mere exchange of information. This study principally investigated interactional metadiscourse markers used in the English speeches of Mr. Tshering Tobgay, the Honourable Prime Minister of Bhutan, delivered to international audiences on a variety of different topics. The present qualitative descriptive research focused on textual analysis using the metadiscourse model of Hyland[2] and the Appraisal theory of Martin and White[3]. The results of the study showed attitude markers ranked the highest followed by engagement markers, self-mentions, boosters, and hedges. Moreover, the study also revealed that the topics of his speeches influenced the use of the interactional metadiscourse markers of the speaker. In general, this study highlighted elements of metadiscourse markers used by the leader of the country in delivering public speeches. The present study contributed to the existing body of literature related to metadiscourse analysis, especially of spoken texts. The information from this research can be of benefit to language learners, teachers and speakers in general, who are passionate about developing speaking skills.Â Â